Influência da suplementação de vitamina D na remodelação ventricular após o infarto do miocárdio - Gonçalves, Andréa de Freitas [UNESP] (2013)
The process of cardiac remodeling after myocardial infarction is associated with poor outcome. In the acute phase, remodeling promotes the formation of the aneurysm and predisposes to ventricular rupture. Chronically, it is associated with higher prevalence of malignant arrhythmias and ventricular dysfunction, because the non infarcted region undergoes genetic, structural and biochemical changes which will result in impairment of functional capacity of the heart and death. Therefore, strategies to attenuate remodeling result in improved prognosis after myocardial infarction. Recent evidence suggests that changes in the levels of vitamin D can result in important cardiovascular actions. Additionally, experimental models suggest that it could modulate cardiac remodeling process. However, the effects of vitamin D supplementation on heart after infarction are not known. In our study, we assessed the effects of vitamin D supplementation on cardiac morphological and functional changes after acute myocardial infarction in rats by studying some of the key mechanisms involved in heart remodeling: hypertrophy and changes in ventricular geometry, functional changes, collagen amount, oxidative stress, energy metabolism, inflammation, apoptosis and changes in the distribution of myosin heavy chains. In our results, we found that infarcted animals that received vitamin D supplementation had higher left ventricle systolic and diastolic diameters increased systolic and diastolic areas associated with decreased fractional area change, ejection fraction and posterior wall shortening velocity, decreased systolic blood pressure, increased apoptosis by increasing the expression of proteins caspase 3 and decreased bcl-2, decreased activity of the enzyme phosphofructokinase. There was no interaction between infarct and vitamin D for myosin heavy chains, metalloproteinase activity, oxidative stress, ICAM-1, IL-10 and TIMP. Thus, we can conclude that vitamin D ...